2021
DOI: 10.1186/s12943-021-01420-9
|View full text |Cite
|
Sign up to set email alerts
|

AMPK promotes antitumor immunity by downregulating PD-1 in regulatory T cells via the HMGCR/p38 signaling pathway

Abstract: Background AMP-activated protein kinase (AMPK) is a metabolic sensor that maintains energy homeostasis. AMPK functions as a tumor suppressor in different cancers; however, its role in regulating antitumor immunity, particularly the function of regulatory T cells (Tregs), is poorly defined. Methods AMPKα1fl/flFoxp3YFP-Cre, Foxp3YFP-Cre, Rag1−/−, and C57BL/6 J mice were used for our research. Flow cytometry and cell sorting, western blotting, immuno-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Indeed, our latest studies identified that concomitant use of Glutaminase inhibitor 968 and anti-PD-L1 remarkably boosted the immune response against ovarian cancer [ 74 ]. Consistent with our findings, combined inhibition of PD-1 and activation of AMPK by Metformin, AICAR or BME had currently been proposed to double response rates in suppressing cell growth of different types of cancers and yielding a substantial increase in the number of tumor-infiltrating CD8 + T cells in mouse models [ 75 , 76 , 77 , 78 ], supporting the potential clinical use of AMPK activators when combined with anti-PD-1 ICIs. Additionally, the retrospective review disclosed better clinical outcomes (ORR, PFS, and OS) in patients with NSCLC who received concurrent Metformin and ICIs [ 79 ].…”
Section: Complementary Targeted Therapeutics—a Double Hit Effect On O...supporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, our latest studies identified that concomitant use of Glutaminase inhibitor 968 and anti-PD-L1 remarkably boosted the immune response against ovarian cancer [ 74 ]. Consistent with our findings, combined inhibition of PD-1 and activation of AMPK by Metformin, AICAR or BME had currently been proposed to double response rates in suppressing cell growth of different types of cancers and yielding a substantial increase in the number of tumor-infiltrating CD8 + T cells in mouse models [ 75 , 76 , 77 , 78 ], supporting the potential clinical use of AMPK activators when combined with anti-PD-1 ICIs. Additionally, the retrospective review disclosed better clinical outcomes (ORR, PFS, and OS) in patients with NSCLC who received concurrent Metformin and ICIs [ 79 ].…”
Section: Complementary Targeted Therapeutics—a Double Hit Effect On O...supporting
confidence: 89%
“…Although PD-1 acts as an important negative feedback regulator of T cell effector functions, the upstream pathway implicated in the downregulation of PD-1 is still unclear. The discovery of the regulation between AMPK phosphorylation and repression of PD-1 is conceivably attributed to the AMPK downstream signalings such as the p38 MAPK/GSK3β axis [ 75 ] and the KEAP1/NRF2 cascade [ 76 , 80 ]. Of note, AMPK activation is thought not only to straightforwardly reduce tumor burden by inhibiting cancer cell growth but also to concurrently support the expansion and survival of tumor-infiltrating lymphocytes (TILs), especially CD8 + T cells within the TME, in part by the inhibition of glycolysis and promotion of oxidative phosphorylation [ 81 , 82 , 83 , 84 ].…”
Section: Complementary Targeted Therapeutics—a Double Hit Effect On O...mentioning
confidence: 99%
“…inhibitor, but also could regulate PD-1 expression, increase expansion of effector T cells, reduce the emergence of immune escape and display antitumor effect in murine tumor models [37][38][39]. Among the remaining genes, Chen et al [40] found that CCNB2 could serve as a marker to predict response to anti-PD-1 therapy in NSCLC patients, suggesting that CCNB2 might also be a predictor of response to anti-PD-1 treatment in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that myeloid-derived suppressor cells (MDSCs) can act as the primary mediators of immune responses in many cancers and other pathological progress. Tregs can regulate immune suppression of anti-tumor immune response in the tumor microenvironment ( Bronte et al, 2016 ; Li et al, 2020 ; Pokhrel et al, 2021 ). DCS identified and processed tumor-associated antigens in the tumor microenvironment and promoted anti-tumor immunity by modulating other immune cells’ functions ( Wculek et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%